Fog simulation on the North coast of Portugal - Senande Rivera, Martin (2019)
The central theme of this study is the numerical simulation of fog events on the north coast of Portugal. The main objective is the identification of the aspects that offer the most scope for improve the simulation of this phenomenon using the atmospheric WRF model. Through a review of the scientific literature related to this topic, two formation processes were identified that seem predominant in areas with meteorological characteristics similar to those of the Portuguese coast: the advection of humid air over cold coastal waters and the propagation towards the surface of low clouds. One of the most important parts of the study is the comparison of the impact of several physical schemes in the simulation of different fog events. Within the different parameterization categories analyzed, the radiation and the planetary boundary layer are the ones that produce the biggest variations in the results. In contrast, the different parameterizations of the microphysics used did not provide significant differences. The performance of a sensitivity test of the SST, which consists in introducing a negative artificial anomaly in the SSTs near the west coast of the Iberian Peninsula, showed that the SST errors will have a much smaller impact than the coice of the physical parametrizations in the simulation of the fog event. In addition, the simulations executed with the SSTs obtained with the oceanic model ROMS reaffirm this hypothesis. Finally, when the dominant formation process of each event was identified, a connection between the formation process and the parameterization that produces better results of each event was observed